2016
DOI: 10.4149/av_2016_04_400
|View full text |Cite
|
Sign up to set email alerts
|

Effect of repeated Ribavirin treatment on grapevine viruses

Abstract: Summary. -The effect of Ribavirin treatment for the chemotherapy of several grapevine viruses was evaluated. Four grapevine cultivars were repeatedly treated with Ribavirin in two different concentrations and with three different lengths of treatment. Repeating the Ribavirin treatment always had a significant effect on the number of healthy grapevine plants obtained. Ribavirin concentration and length of exposure showed a significant difference in sanitation of the Grapevine rupestris stem pitting-associated v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…To the best of our knowledge, there is no data available on GRVFV, GSyV-1, GVT, and GPGV being eliminated through somatic embryogenesis. Some grapevine cultivars infected with GPGV were successfully sanitized by the meristem culture with or without heat therapy [28], or by repeated treatment with ribavirin for 8 to 16 weeks [29], but we are not aware any reported for elimination of GRVFV, GSyV-1 and GVT. It is challenging to eliminate GRSPaV [5], and traditional virus elimination methods showed very variable efficiency [21,30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, there is no data available on GRVFV, GSyV-1, GVT, and GPGV being eliminated through somatic embryogenesis. Some grapevine cultivars infected with GPGV were successfully sanitized by the meristem culture with or without heat therapy [28], or by repeated treatment with ribavirin for 8 to 16 weeks [29], but we are not aware any reported for elimination of GRVFV, GSyV-1 and GVT. It is challenging to eliminate GRSPaV [5], and traditional virus elimination methods showed very variable efficiency [21,30].…”
Section: Discussionmentioning
confidence: 99%
“…The artificial infection of grapevines with particular viruses for virus indexing is very difficult and time-consuming, which is why systematic tests of the efficiency of virus elimination methods are highly demanding. The advantages of the meristem culture can be combined with chemotherapy, thereby helping to overcome these technical challenges [29], but these methods are not only dependent on the virus, but also on the genotype of the host plant, which makes this picture more complex. Virus elimination with somatic embryogenesis offer very useful possibilities.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, 13 GFkV-infected preclonal candidates were included into the sanitation process and 26 regenerants were obtained, which were all free of GFkV. Complete elimination was also achieved with somatic embryogenesis [10], repeated ribavirin treatment [13,45], the combination of ribavirin and oseltamivir [14], and ribavirin combined with thermotherapy [24]. Two fleck-similar viruses, GRVFV and GSyV-1, were detected for the first time in Slovenia; GRVFV was significantly more abundant [46].…”
Section: Discussionmentioning
confidence: 94%
“…In our previous study [40], GPGV was the most prevalent virus with 91.14% of infected vines included in the study, for which 26 samples were selected for therapy and all 49 regenerated plants were GPGV-free. Successful elimination has also been achieved through somatic embryogenesis [10] and repeated treatment with ribavirin [13]. Previous studies [27,42,54] indicated that GRSPaV and RBDV are difficult to eliminate in grapevines and raspberries, respectively, whether by thermotherapy, a meristem/shoot tip culture, or their combination, because they are presumed to infect meristematic tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation